The mechanism of PDE7B inhibiting the development of hepatocellular carcinoma through oxidative stress - Luo, Yunfeng; Gao, Huaide; Zhao, Jianghua; Chen, Lin; Shao, Jianguo; Ju, Linling (Frontiers in Immunology, 2024)
BackgroundLiver cancer presents a significant challenge to global health and is currently ranked as the sixth most common form of cancer worldwide. Recent research indicates that phosphodiesterases play a role in various physiological and pathological processes, with a specific focus on their impact on cancer advancement. There is a scarcity of studies investigating the function and mechanisms of phosphodiesterases in the development and progression of hepatocellular carcinoma (HCC).MethodsReal-time fluorescence quantitative polymerase chain reaction (qRT-PCR) and Western blotting were employed to analyze the expression of PDE7B in hepatocellular carcinoma tissues and cells. The biological role of PDE7B in HCC was investigated by both overexpressing and knocking down PDE7B in liver cancer cell lines. Furthermore, potential target proteins of PDE7B were identified through transcriptome sequencing.ResultsPDE7B is conspicuously reduced in tissues and cells of hepatocellular carcinoma, showing a connection with an unfavorable prognosis. Inhibiting PDE7B boosts the growth, movement, and infiltration of liver cancer cells, while its increased expression has the reverse impact. According to our trials relating to oxidative stress, PDE7B appears to control cell death in liver cancer cells by impacting the production of reactive oxygen species. Therefore, we propose that PDE7B could hinder the initiation and advancement of HCC through an oxidative stress pathway.ConclusionThe research we conducted reveals that PDE7B, a gene with minimal levels of activity in hepatocellular carcinoma, possesses the capacity to inhibit the proliferation, invasion, and migration of HCC cells. PDE7B can impact the development of hepatocellular carcinoma by adjusting mechanisms related to oxidative stress.